Desenvolvimento de bebida vegetal à base de amêndoa de castanha de caju (Anacardium occidentale L.), arroz (Oryza sativa L.) e ameixa (Prunus domestica L.) - Pinto, Daiane dos Santos (2021)
Foods that are beneficial for health and that meet the needs of people with dietary restrictions have sparked consumer interest. In this sense, vegetable beverage are a healthy alternative, since they are free of animal fat, lactose and gluten, they are rich in antioxidants, fibers and insaturated fats. Thus, this study aimed develop vegetable beverage based on almond cashew nut, rice and plum. Four formulations were defined through factor planning 22 , varying cashew nut and plum, being (BV1: 3% cashew nut + 9% plum); (BV2: 6% cashew nut + 9% plum); (BV3: 3% cashew nut + 12% plum); (BV4: 6% cashew nut + 12% plum). The beverage were analyzed for physical-chemical characterization, carotenoid content, antioxidant activity, apparent viscosity, rheology, colorimetric evaluation, fatty acid profile, microbiological analysis of coliforms at 35 ºC, coliforms at 45 ºC and Salmonella spp. The sensory evaluation was carried out with 77 tasters, using acceptance test with hedonic scale. BV1 formulations exhibited higher moisture, while BV2, showed higher values crude fiber (0.93%). BV3 formulations, exhibited lower pH (4.42) and higher antioxidant activity (3.67 µM trolox / mL). Beverages added with 6% cashew nuts were the most viscous. The main fatty acids identified were oleic, palmitic and stearic acid. Beverages showed pseudoplastic non-Newtonian fluid behavior. The addition of larger quantities of plum and smaller amounts cashew nuts gave a dark color, with BV3 formulations showing the darkest color (L*=43.22). In the microbiological analysis, low coliform counts were detected at 35ºC, coliforms at 45ºC (<3 NMP.mL-1 ) and absence of Salmonella spp. The beverages obtained good sensory acceptance with scores between 6.14 to 7.23, but there was no significant difference (p≤ 0.05) between them. It is concluded that the development of a new vegetable beverage based on rice, cashew nut and plums is viable. In addition, the use of different concentrations of plum and cashew nut enabled the production a product with excellent source nutrients, with good profile lipid, microbiologically safe and accepted sensorially